2019
DOI: 10.3390/w11020247
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Collapse of Multiple Bubbles and the Energy Conversion during Bubble Collapse

Abstract: This paper investigates numerically the collapses of both a single cavitation bubble and a cluster consisting of 8 bubbles, concerning mainly on the conversions between different forms of energy. Direct numerical simulation (DNS) with volume of fluid (VOF) method is applied, considering the detailed resolution of the vapor-liquid interfaces. First, for a single bubble near a solid wall, we find that the peak value of the wave energy, or equivalently the energy conversion rate decreases when the distance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…1 [73]) or the shock wave energy (E SW ) generated from bubble collapse (eq. 2 [74]) need not only to exceed the friction force but to also move the particle away from the membrane.…”
Section: Effects Of Ultrasound On Foulingmentioning
confidence: 99%
“…1 [73]) or the shock wave energy (E SW ) generated from bubble collapse (eq. 2 [74]) need not only to exceed the friction force but to also move the particle away from the membrane.…”
Section: Effects Of Ultrasound On Foulingmentioning
confidence: 99%
“…However, a consensus has not yet been reached for the mechanism of energy conversion during collapse. Zhang et al believe that the energy of a bubble is transformed into the wave energy of its fluid, causing an impact on a solid wall [24]. Qin found that when a bubble collapses, there is a large amount of heat transfer and energy exchange between the bubble and the outside [23].…”
Section: Bubble At the Wallmentioning
confidence: 99%
“…Shockwave pressure causing cavitation erosion on a solid wall is a concerning issue. Zhang showed that during the collapse of a single bubble, the greatest impact on the wall is the p 2ndmax , which is caused when the bubble is completely collapsed [24]. For laserinduced thermal cavitation bubbles, the initial input energy will also cause extremely highpressure shock p 1stmax .…”
Section: Bubble At the Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al . [12] studied the conversion relationship between cavitation bubble potential energy and wave energy during the collapse of cavitation bubbles near the wall. Han et al .…”
Section: Introductionmentioning
confidence: 99%